2022
DOI: 10.1177/2156759x221110803
|View full text |Cite
|
Sign up to set email alerts
|

“Where I Can Be Myself”: Black Youth Narratives of Their Future Careers

Abstract: This qualitative study centers on the career narratives of seven Black youth enrolled at an urban public school in the Midwest. We used critical race theory to analyze participants’ responses to a narrative career counseling intervention, My Career Story (Savickas & Hartung, 2012). The four interconnected themes found were (a) persistence against all odds, (b) unconditional acceptance and connections, (c) self-advocacy, and (d) tranquility. We discuss direct implications for school/career counselors and sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…And although not all of the school counselors who facilitated the interventions were Black, both those from White and Black racial backgrounds infused Blackness into their interventions. We add to previous scholars’ calls for interventions created within school settings to confront racism (Byrd et al, 2022; Day-Vines & Day-Hairston, 2005; Franklin & Pack-Brown, 2001; Washington, 2021) and we challenge those who understand the efficacy of groups to create homeplace for our students.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…And although not all of the school counselors who facilitated the interventions were Black, both those from White and Black racial backgrounds infused Blackness into their interventions. We add to previous scholars’ calls for interventions created within school settings to confront racism (Byrd et al, 2022; Day-Vines & Day-Hairston, 2005; Franklin & Pack-Brown, 2001; Washington, 2021) and we challenge those who understand the efficacy of groups to create homeplace for our students.…”
Section: Discussionmentioning
confidence: 93%
“…Prior studies have reported barriers to facilitating small groups in schools, but those barriers did not consider PPI (Steen et al, 2007). Fighting racism and offering opportunities for students of color to thrive and dream about future opportunities may generate forms of resistance (Byrd et al, 2022). While scholars are producing creative, innovative, and fresh models to gather student voices (Edirmanasinghe et al, 2022b), we still need further clarity on engagement strategies school counselors use to overcome barriers and resistance in doing antiracist work.…”
Section: Discussionmentioning
confidence: 99%
“…This ideology ignores the presence of racism and ultimately protects whiteness as a cultural norm and the dominant sociopolitical influence (i.e., power) that comes with whiteness (Ladson-Billings & Tate, 1995;Solórzano & Yosso, 2002). Byrd et al (2022) The final tenet, intersectionality, a term coined by legal scholar Kimberlé Crenshaw (1989), explores the interconnectedness of oppression when racism is combined with other forms of subjugation (ie. sexism, homophobia, classism, and ableism).…”
Section: Critical Race Theorymentioning
confidence: 99%
“…While many scholars justly argue that racism is inextricably woven into our educational structures and is untreatable (Givens, 2016;Watkins, 2001), others hopefully look to CRT as a tool to dismantle structures of oppression (Ladson-Billings & Tate, 1995). Many K-12 education and school counseling scholars utilize CRT and encourage others to deploy it as a lens to support research, practice, and advocacy efforts (Appling & Robinson, 2021;Byrd et al, 2022;Henfield & Washington, 2012). Unfortunately, school counseling research overall has largely ignored these suggestions.…”
Section: Critical Race Theory In Education and School Counselingmentioning
confidence: 99%
See 1 more Smart Citation